Are Most of the Published Clinical Trial Results in Restorative Dentistry Invalid? An Empirical Investigation - Mickenautsch, Steffen (Reviews on Recent Clinical Trials, 2020)
Background: To establish the number of invalid clinical trial reports in restorative dentistry, due to lack of effective randomisation and/or inadequate sample size and whether this number changed, during the 1990-2019 period. Methods: Databases were searched up to 14 July 2019 without limitations regarding publication language. A Journal hand search and reference check were conducted for trial reports. Selection criteria were: reporting on a prospective, controlled clinical trial; relevance to placing direct tooth restorations in human vital teeth; direct comparison between restorative materials concerning tooth restoration longevity; trial report published from 1990. Randomisation reported (Yes/No) and treatment group sample size ≥ 200 were applied as criteria, using the deductive falsification approach for trial report appraisal. Results: 683 trial reports were appraised. 660 lacked effective randomisation. Of the remaining 23 reports, only 2 included a sample size of more than 200 restored teeth (mean number per treatment group 87; Standard deviation = 108.51). 92.5% of all treatment groups had a sample size of < 200. Randomisation reporting increased and sample size remained essentially unchanged between 1990 and 2019. Conclusion: Most of the published clinical trial results in restorative dentistry were judged invalid, due to lack of effective randomisation and adequate sample size. These results are in line with previous findings. Evidence-based recommendations on how to improve trial methodology are available in the dental/medical literature.
Keywords: dental/medical literature